¬PENGARUH MOTIVASI KERJA, INSENTIF DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN DI PT WORLD INNOVATIVE TELECOMUNICATION DENPASAR - Ni Nyoman Ayuk Krisna Jayatri; Ni Nyoman Suryani; Putu Pradiva Putra Salain (EMAS, 2022)
Business development and competition between companies make the company must improve and develop their performance. Seeing such a situation, company leaders are always required to act professionally in an effort to achieve the company's goals in the midst of intense business competition. This research aims to find out the influence of work motivation, incentives and work environment on employee performance at PT World Innovative Telecomunication in Denpasar. This study uses total sampling technique with 82 respondents as the research sample, then through the results of the distribution of questionnaires to all respondents analyzed using multiple linear regression analysis techniques with a statistical application program, SPSS 25.0 For Windows. The results of the research explained that (1) Work motivation has a positive and significant effect on employee performance at PT World Innovative Telecomunication Denpasar. By improved the employee work motivation, it will be able to improve employee performance at PT World Innovative Telecomunication Denpasar. (2) Incentives have no significant effect on employee performance at PT World Innovative Telecomunication Denpasar. The results of this study explained that the distribution of incentives at PT World Innovative Telecomunication Denpasar did not affect the improvement of employee performance at PT World Innovative Telecomunication Denpasar. (3) The work environment has a positive and significant effect on employee performance at PT World Innovative Telecomunication Denpasar. The results of this study explain that if attention to the employee work environment increases it will affect the increasing employee performance at PT World Innovative Telecomunication Denpasar.